Rancang Bangun Sistem Tracking Matahari berdasarkan Cahaya dan Arus pada Sel Surya menggunakan Logika Fuzzy Model Sugeno - Yunan Alamsyah Nasution; Dahnial Syauqy; Barlian Henryranu Prasetio (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Electricity is one of the most demand energy nowadays, demand for electricity has come greater year by year. With the increasing demand for electrical energy, the need for fulfillment of enviromentally friendly energy. One way is to use solar panels. However, the effectiveness of solar panels will be reduced if their position is not perpendicular to the direction of the sun's rays. Based on the problem, writer want to make a system that can increase solar panels effectivity with detecting where sun ray come with LDR sensors, and the system can move the solar panel in the direction of sun ray comes with servo motor. Data gathered from each sensors will be processed in the Arduino Uno with Fuzzy Logic and then Arduino Uno will send a signal to servo motor to move according to calculations that has been done before. Based on testing, after solar fuzzy system installed on the solar panel, the effectiveness of solar panels increased by 13,427%.